The tragic state of the Congo : from decolonization to dictatorship - Haskin, Jeanne M., 1964- (Algora Pub., 2005)
The Congo is rich in minerals and agricultural potential. What keeps it from emerging as a viable, even prosperous, state? During four centuries of the slave trade, the Portuguese alone claimed over 13.25 million lives. Then, King Leopold II of Belgium took the Congo as his own fiefdom in 1876, and the exploitation of the populace was even more horrendous. The Belgian Congo was ruled by the Church and the State in cooperation with private companies. Education peaked at the secondary level, to deter the Congolese from aspiring to leadership roles. In many cases, children were taken at an early age and impressed into King Leopold's army, the Force Publique. Independence in 1960 did not end the conflict with Belgium, but it did bring a new chaos as the local population struggled to run their fledgling country. When the stakes are so high, division and conflict are easily provoked. Under the influence of ambitious leaders and outside interests, the problems escalated. Patrice Lumumba, the first prime minister (and suspected of communist leanings), was assassinated. After five years of turmoil, Colonel Mobutu rose to power -- with help from the United States. Mobutu ruled the country (then called Zaire) through a one-party state that co-opted the people with fanciful slogans and empty promises. It was also a police state whose reach extended into every school and every village. Atrocities were committed to strike fear into the people; furthermore, Mobutu's response to the genocide in Rwanda was to allow the Hutu génocidaires to take up residence in Zaire. This led to clashes with the Zairian Tutsis and with Rwanda and Burundi. Interference by outside powers who covet Congo's resources only exacerbates regional rivalries. Today, every intervention in the name of "assistance" seems to raise new questions about motives and allegiances, and the lives of hundreds of thousands of people continue to be at risk.